Influência da pluviosidade na fauna acompanhante de crustáceos decapoda (pleocyemata): um estudo de caso - Nascimento, Itacilha Mozana do (2019)
The predatory fishing activity of shrimp is responsible for the modification of the benthic environment, which is home to thousands of species, mainly due to the enormous number of organisms captured as bycatch. The aim of this study was to analyze the influence of rainfall on the accompanying fauna of Decapoda (Anomura and Brachyura) and their relationship with environmental factors captured on the coast of Rio Grande do Norte - Brazil. The collection of biological material and measurement of variables (depth, transparency, temperature, pH, salinity, sand, clay and algae) was carried out using trawls using a motorized craft (door drag) carried out in Baia Formosa. Five random trawls were carried out monthly, from January to December 2016, in the traditional shrimp fishing area. 253 individuals from 16 species and 8 families were captured, which are the family Portunidade, Calappidae, Leucosiidae, Aetheridae, Panopeidae, Epialtidae, Diogenidae and Porcellanidade.